2021
DOI: 10.1016/j.bjpt.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and beliefs on low back pain in physical therapy education: A cross-sectional study

Abstract: Background: Prescription behavior in low back pain (LBP) differs between physical therapists with a biomedical versus a biopsychosocial belief, despite the presence of clinical guidelines. Objective: To examine (1) the beliefs of physical therapy students and their adherence to clinical LBP guidelines in Belgium and the Netherlands; (2) whether the beliefs and attitudes of physical therapy students change during education; (3) whether beliefs are related to guideline adherence; (4) whether beliefs and attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
1
17
0
3
Order By: Relevance
“…A more pronounced biomedical orientation (indicating a belief that pain and disability result from a specific structural impairment and that treatment should be selected to address this impairment) negatively influences patient outcomes, resulting in less compliance with the clinical practice guidelines for LBP. [1][2][3] In Japan, Takasaki et al 4) found that therapists credentialed in Mechanical Diagnosis and Therapy (MDT), an internationally standardized postgraduate clinical qualification, were more biopsychosocially oriented and less biomedically oriented than other physical therapists. It was also found that possession of a postgraduate academic degree was a contributing factor for compliance with clinical practice guidelines in examinations using established clinical vignettes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more pronounced biomedical orientation (indicating a belief that pain and disability result from a specific structural impairment and that treatment should be selected to address this impairment) negatively influences patient outcomes, resulting in less compliance with the clinical practice guidelines for LBP. [1][2][3] In Japan, Takasaki et al 4) found that therapists credentialed in Mechanical Diagnosis and Therapy (MDT), an internationally standardized postgraduate clinical qualification, were more biopsychosocially oriented and less biomedically oriented than other physical therapists. It was also found that possession of a postgraduate academic degree was a contributing factor for compliance with clinical practice guidelines in examinations using established clinical vignettes.…”
Section: Introductionmentioning
confidence: 99%
“…A more pronounced biomedical orientation (indicating a belief that pain and disability result from a specific structural impairment and that treatment should be selected to address this impairment) negatively influences patient outcomes, resulting in less compliance with the clinical practice guidelines for LBP. 1 , 2 , 3 )…”
Section: Introductionmentioning
confidence: 99%
“…As previously indicated, professional education behaves as a key element in introducing new biopsychosocial paradigms of LBP care paradigms into clinical practice. Currently, new works such as Leysen et al (2021) and found useless beliefs about back sensitivity and the need for protection among physiotherapy students and developed crosssectional studies to evaluate changes in attitudes and beliefs during their training [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that LBP beliefs are already present in the emerging HCP workforce [ 16 ], which suggests that educational factors play an important role in the formation of such beliefs. To date, beliefs related to LBP have been investigated in students enrolled in HCP disciplines such as physiotherapy (PT) [ 17 21 ], medicine [ 22 24 ], nursing [ 17 , 19 , 20 ], pharmacy [ 22 ], chiropractic [ 22 ], occupational therapy (OT) [ 19 , 22 ], and midwifery [ 23 ].…”
Section: Introductionmentioning
confidence: 99%